A perfect hand - Waldman, Ayelet (Alfred A. Knopf, 2026)
A richly drawn, captivating, and endlessly amusing novel of love and subterfuge between a lady's maid and her clandestine lover, set in the country estates of nineteenth-century England. Miss Alice Lockey, daughter of a tenant farmer, has by dint of hard work, innate intelligence, and a cunning ability to predict the moods of her betters, raised herself to the lofty status of lady's maid at Alderwick Park. Though her mother has advised Alice to work only until marriage, Alice has thus far resisted the temptations of matrimony among the neighboring widowers and pig farmers, more content to enjoy the fruits of her labor: or at least the portion of it her father will share after it is paid to him. Alice spends her days arranging Lady Jemima Alderwick's blond hair into the latest French styles, chignons and plaits, laundering her lady's surprisingly malodorous petticoats and drawers, and carefully sewing all manner of fripperies, ribbons, lace, and silk flowers, to her lady's bonnets and gowns. But when a visiting servant, a valet named Charlie Wells, catches her eye, Alice begins to understand the constraints of her position. In a ploy to spend time with the object of her affection, Alice attempts to arrange a romance between Lady Jemima Alderwick and Charlie's employer, one Baronet Sir Nigel Wynstowe. If only they would fall in love: then Alice and Charlie might live together as man and wife! Challenged by Lady Jemima's love for another and Sir Wynstowe's eccentric personality, Alice must use all of her cunning to bring about this unlikely romantic union. Will this low-born servant successfully manipulate the hearts of these lords and ladies? Will Charlie and Alice ever improve their stations? Or, as the beginning of women's suffrage begins to percolate in the drawing rooms and salons of London, will Alice discover a different sort of path for herself? A deliciously funny, gorgeously detailed, utter enthralling novel, A Perfect Hand is a glorious novel of class, gender, and England on the cusp of enormous change.